The Open Source and the water oxygenation in the intensive breeding of “Paco” (Piaractus brachypomus) - Panduro Alvarado, Leyber (2023)
Objective. The study sought to analyze the oxygenation of water in the intensive breeding of “Paco” applying the Open Source. Methods. An explanatory study was carried out, whose population was constituted by the fish-farms of Agropecuaria Ebenezer, in the el Fundo Ecológico La Colorada, in the Ucayali region (Peru). It developed the installation of a method for control and collection data on dissolved oxygen, using a computer program that activated the Venturi system, which in turn activated the oxygenation system, controlled by an Arduino microcontroller system. Results. It determined the influence of the Arduino shield on the water oxygenation process for the intensive breeding of “Paco”, allowing the use of clean energy; Likewise, it was possible to know the differentiated results in the production of the intensive breeding of the “Paco”, according to the oxygenation of the water. Conclusions. It achieved determined that the application of Open Source allowed better oxygenation of the water in the breeding of “Paco”, reaching an improvement greater than 2.2 mg/l, and reaching a minimum value of 6.44 mg/l in its application.